Symbolic interactionism, role-identities, and delinquency: examining the moderating role of social rewards - O'Neill, Jennifer (Journal of crime and justice, 2023)
Criminological research consistently supports that reflected appraisals in various domains predict delinquency, yet, extant work has not fully explored theoretical nuances outlined in traditional symbolic interactionism, specifically concerning how conditioning factors are involved in role-taking among peers. This study assesses whether social rewards moderate the association between reflected appraisals and delinquency in order to elucidate the role-taking process and explore a possible mechanism of peer influence on offending. Using data from the National Youth Survey, analyses estimate the relationship among adolescents’ ‘rule violator’ and ‘sociable’ identities from the perspective of peers, perceptions of social rewards, and their count number of delinquent acts. The findings demonstrate mixed support for moderation hypotheses. Perceptions of greater social rewards for delinquency increase the positive association between the sociable appraisal and delinquency, while this interaction occurs in the opposite direction for the association between the rule violator appraisal and delinquency. These results support that social rewards influence behavior differently based on the content of reflected appraisals. This implies a process in which adolescents consider different factors to define delinquency as consistent with the identity they enact among peers; furthermore, the results identify directions for research incorporating the symbolic interactionist perspective in criminology.